2021
DOI: 10.31234/osf.io/ae6t9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of social interactions on momentary stress and mood during COVID-19 lockdowns

Abstract: BACKGROUND: Social interactions are vital for our wellbeing, particularly during times of stress. PURPOSE: We investigated the real-time effect of social interactions on changes in stress and mood using an ecological momentary assessment approach in 732 participants during COVID-19 lockdown in spring 2020 and in a subsample of these participants (n= 281) during a further lockdown in winter 2020. METHODS: Participants reported their stress and mood in a smartphone app five times per day for seven days and indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…This is consistent with existing theories that close social interaction is a fundamental human need and that older adults' close social relationships are generally emotionally satisfying [4,9]. Our findings also echo the empirical within-person evidence that social interactions are central to wellbeing [29], which also held true during the first few months of the COVID-19 pandemic [48,49]. It is also important to note that moments not interacting with anyone were associated with lower PA, but not higher NA.…”
Section: Plos Onesupporting
confidence: 90%
“…This is consistent with existing theories that close social interaction is a fundamental human need and that older adults' close social relationships are generally emotionally satisfying [4,9]. Our findings also echo the empirical within-person evidence that social interactions are central to wellbeing [29], which also held true during the first few months of the COVID-19 pandemic [48,49]. It is also important to note that moments not interacting with anyone were associated with lower PA, but not higher NA.…”
Section: Plos Onesupporting
confidence: 90%
“…Alternatively, lockdown may exacerbate the impact of having social interactions on loneliness (Kuczynski et al, 2022), such that people benefit from social interaction most when they are isolated from others. Indeed, research points to the importance of staying socially connected while physically isolating: social interaction quantity and quality have been shown to predict better mental health outcomes during COVID-19 (Forbes et al, 2021;Nitschke et al, 2021;Sommerlad et al, 2021).…”
Section: Social Experiences During Covid-19mentioning
confidence: 99%
“…These findings suggest that social interactions, or simply the presence of others, can be invigorating. This could be especially important in everyday life, where having the potential to interact with someone, particularly in person (Forbes et al, 2021), may be an important factor for mitigating the detrimental effects of social isolation on energy levels. Indeed, we found that participants who lived alone during the lockdown were most affected by isolation in terms of their energy levels compared to those who lived with others.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, during the baseline day, participants in the lab engaged in social interactions remotely rather than in person. Given the importance of face-to-face interactions for our daily stress and mood (Forbes et al, 2021), future isolation studies could reveal more robust changes in psychological states following isolation, if participants are able to interact in person during the baseline session. However, it is worth emphasising that we found reliable effects of social isolation on energy despite our baseline condition including remote, rather than in person, interactions.…”
Section: Discussionmentioning
confidence: 99%